Individuals and identity in economics - Davis, John Bryan (Cambridge : Cambridge University Press, 2011)
This book examines the different conceptions of the individual that have emerged in recent new approaches in economics, including behavioral economics, experimental economics, social preferences approaches, game theory, neuroeconomics, evolutionary and complexity economics, and the capability approach. These conceptions are classified according to whether they seek to revise the traditional atomist individual conception, put new emphasis on interaction and relations between individuals, account for individuals as evolving and self-organizing, and explain individuals in terms of capabilities. The method of analysis uses two identity criteria for distinguishing and re-identifying individuals to determine whether these different individual conceptions successfully identify individuals. Successful individual conceptions account for sub-personal and supra-personal bounds on single individual explanations. The former concerns the fragmentation of individuals into multiple selves; the latter concerns the dissolution of individuals into the social. The book develops an understanding of bounded individuality, seen as central to the defense of human rights.
Introduction : the individual in economics -- Psychology's challenge to economics : rationality and the individual -- Multiple selves and self-control : contextualizing individuality -- Social identity and social preferences in the utility function -- The individual in game theory : from fixed points to experiments -- Multiple selves in interaction : teams and neuroscience -- Evolution and the individual : identity through change -- Evolution and capabilities : human heterogeneity -- The identity of individuals and the economics of identity -- Economic policy, democracy, and justice.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Economics -- Psychological aspects; Individualism; Economic man; Interpersonal relations; Identity (Philosophical concept)